Selected Contributions on Statistics and Data Science in Latin America : 33 FNE and 13 CLATSE, 2018, Guadalajara, Mexico, October 1-5 /: 33 FNE and 13 CLATSE, 2018, Guadalajara, Mexico, October 1-5. (©2019) - Unknown
No abstract available